Influence of cultivar selection on blast and brown spot diseases in rice: Molecular screening of blast resistance genes - Suvanthini, T.; Weerasena, O.V.D.S.J.; Kottearachchi, N.S.; Fernando, H.N.S.; Silva, J. N. (National Science Foundation of Sri Lanka, 2024)
The prevalence of blast and brown spot diseases in rice is a substantial threat to national food security. This study investigated the distribution patterns of blast and brown spot, comparing their occurrence and distribution with respect to cultivar selection and conducting molecular screening for the identification of blast resistance genes. The research was conducted over five cultivating seasons from Yala 2017 to Yala 2019 in the Northern Province of Sri Lanka. Incidence percentages of the two diseases were calculated in 114 randomly selected fields across the five districts; Jaffna, Mullaitheevu, Kilinochchi, Mannar, and Vavuniya. Molecular markers were used to screen for nine major blast-resistant genes in 25 commonly cultivated rice cultivars. The results showed a significant shift in the disease over the period of study. While blast disease incidence declined after Maha 2017, brown spot incidence increased steadily from Yala 2017, peaking in Yala 2019. Interestingly, farmers’ cultivar preferences, often diverging from the Department of Agriculture recommendations, exhibited a strong correlation with disease occurrence. The cultivar Attakkari was identified as a highly susceptible cultivar, which had only three R genes and a major contributor to the progression of blast before Maha 2017. Despite higher brown spot incidence percentages observed in cultivars At362, Bw367, and Bg450, compared to Bg360, intensive post-Maha 2017 cultivation of Bg360 increased the average brown spot incidence to 43%. Cultivars grown after Maha 2017, with over five R genes, showed lower blast disease incidence, suggesting a genetic link to susceptibility. This lower incidence of blast was also observed in the disease evaluation test, where we used the same cultivars. Hence, this study highlights rice cultivar selection as a decisive factor influencing disease occurrence. Given Sri Lanka’s robust germplasm for blast-resistant genes, strategic cultivar selection has the potential for effective disease management.
Keywords: Blast disease; Brown spot disease; Cluster analysis; Cultivar selection; Molecular screening; Rice cultivars